Characteristics and prognosis of patients with Edwardsiella tarda bacteremia at a single institution, Japan, 2005-2022 - Kohei Hasegawa; Murata Kenya; Kumiko Suzuki; Yoshihiko Ogawa (BMC, 2022)
Abstract Background Edwardsiella tarda is a member of Enterobacteriaceae isolated from freshwater and sea. E. tarda infection in humans commonly causes gastroenteritis, but rarely causes bacteremia. However, few studies have described the clinical features of E. tarda bacteremia (ETB); therefore, we conducted a case review in our hospital. Methods We conducted a single-center, retrospective descriptive study using electronic medical records. Patient and microbial features were extracted and evaluated for 30- and 90-day mortality rates. Results From April 2005 to April 2022, the total set of blood cultures positive for any microorganisms was 9368, 38 of which were positive for E. tarda. Underlying cancer was observed in 65.8% of patients. The most common source of bacteremia was cholangitis, followed by cholecystitis, and endoscopic or surgical drainage was performed in almost all cases. Diarrhea was observed in only one patient, and there were no cases in which gastroenteritis was the source of bacteremia. All cases, except for one, were susceptible to all β-lactams, such as ampicillin. The 30- and 90-day overall mortality rates were 8.6% (3/35) and 25.8% (8/31). Of these, 75% patients died because of cancer progression after successful ETB treatment. Conclusion ETB may occur in patients with malignant underlying conditions. Biliary tract infections are common in ETB cases, whereas gastroenteritis may be an atypical cause of bacteremia. This study suggests that although the mortality rate for ETB at 30 day was low, it increased at 90 day as a result of the development of unfavorable underlying conditions.